#TITLE_ALTERNATIVE# - Mega Rahmadani (NIM 10103036), Efo
ABSTRACT: Secret sharing scheme is a method used to secure a secret by sharing or distributing the secret to some participants. To increase the security, a secret showed in a coloring pattern of a graph is encrypted. The encryption process is based on a system of public key cryptography. In this case, the graph structure is a public key, while proper n-coloring of the graph is a private key. The graph n-coloring problem is a special case of public key cryptography Polly Cracker, that known as a NP-complete problem. So that, this scheme is expected to have a good security level, thus it will be difficult enough to attack.